Experimental Investigation on the Friction-Induced Vibration with Periodic Characteristics in a Running-In Process under Lubrication - Di Sun; Pengfei Xing; Guobin Li; Hongtao Gao; Sifan Yang; Honglin Gao; Hongpeng Zhang (Shock and Vibration)
This paper investigated the friction-induced vibration (FIV) behavior under the running-in process with oil lubrication. The FIV signal with periodic characteristics under lubrication was identified with the help of the squeal signal induced in an oil-free wear experiment and then extracted by the harmonic wavelet packet transform (HWPT). The variation of the FIV signal from running-in wear stage to steady wear stage was studied by its root mean square (RMS) values. The result indicates that the time-frequency characteristics of the FIV signals evolve with the wear process and can reflect the wear stages of the friction pairs. The RMS evolution of the FIV signal is in the same trend to the composite surface roughness and demonstrates that the friction pair goes through the running-in wear stage and the steady wear stage. Therefore, the FIV signal with periodic characteristics can describe the evolution of the running-in process and distinguish the running-in wear stage and the stable wear stage of the friction pair.